Gods and heroes of Huarochirí - Cerrón-Palomino, Rodolfo (2021)
Despite the fact that more than half a century has passed since the appearance of the Arguedian translation of the Huarochiri manuscript, a systematic study of onomastics (anthroponymy and toponymy) has not yet been undertaken, even in the subsequent efforts to offer more philologically careful versions of the text, which energizes and delimits it in narrative time and space. In this contribution we will try to etymologize some of the names of the gods and heroes that populate the textual universe of the manuscript. To this end, as in all disciplined etymological research, we will try to be guided by the unavoidable methodological principles and postulates of historical linguistics and philology.